Modified multicarrier sinusoidal pulse-width modulation for three-phase open-load five-level inverter - Suroso, Suroso; Prasetijo, Hari; Susilawati, Hesti; Murdyantoro Am, Eko; Mubyarto, Agung (Institute of Advanced Engineering and Science, 2024)
Five-level voltage source inverter (VSI) is a power inverter topology generating a five-level output voltage waveform. This inverter topology can reduce harmonics distortion to be lower compared to a conventional two-level inverter. In practical, delay of gating signals is unavoidable during switching operation of power semiconductor switches. Adding dead time in the gating signals of VSI’s power switches is mandatory to avoid short circuit during switching operation. However, the dead time of the inverter’s switching signals causes low frequency harmonics and distortion of inverter’s output waveforms. In this paper, a different multicarrier sinusoidal pulse-width modulation (SPWM) method with harmonics suppression capability was proposed and applied in the three-phase open-connection load five-level inverter. The proposed modified SPWM was tested using computer simulation of Powersim (PSIM) software. The measured output waveforms of the five-level VSI at different power factor conditions are presented and analyzed. The total harmonics distortion (THD) values of inverter’s output current were suppressed using the proposed SPWM method to be less than 1%. The test results showed that the proposed modified SPWM method was able to reduce the distortion (THD) of alternating current (AC) waveform, and increase the quality of the inverter’s output power.